1978
DOI: 10.2172/6941692
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for codes and standards to be used for design and fabrication of high level waste canister

Abstract: Approved by:-. hh, (6) Development. o f preliminary c a n i s t e r closure desig'n concepts for c a n i s t e r s which meet al.1 applicable codes i d e n t i f i e d i n (a); and, (c) Determination o f . a t e s t i n g . . program necessary f o r c a n i s t e r design v e r i f i c a t i o n .To complement t h e above, t h i s study includes i d e n t i f i c a t i o n of qua1 i t y assurance standards t o be applied t o the des,ign, fabrication, and t e s t i n g o f the canister.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1978
1978

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Reasons which have been forwarded for routine overpacking include: 1) to provide a stress-free outer canister (this requires stress relief of the seal weld area), 2) to assure low surface contamination of the outer canister, or 3) to provide redundant protection, e.g., the overpack canister could be of a different material, selected to counterbalance weaknesses (to chloride attack, for instance) in the protection afforded by the primary canister. However, a recent study concluded, "... the use of an overpack, as an integral part of design results in an undesirable design and economic constraint on the waste management system" (Bermingham, 1978).…”
Section: Compatibility With Overpackingmentioning
confidence: 99%
“…Reasons which have been forwarded for routine overpacking include: 1) to provide a stress-free outer canister (this requires stress relief of the seal weld area), 2) to assure low surface contamination of the outer canister, or 3) to provide redundant protection, e.g., the overpack canister could be of a different material, selected to counterbalance weaknesses (to chloride attack, for instance) in the protection afforded by the primary canister. However, a recent study concluded, "... the use of an overpack, as an integral part of design results in an undesirable design and economic constraint on the waste management system" (Bermingham, 1978).…”
Section: Compatibility With Overpackingmentioning
confidence: 99%